Left ventricular function in elite rowers in relation to training-induced structural myocardial adaptation. - Mantziari, A; Vassilikos, V; Giannakoulas, G; Karamitsos, T; Dakos, G; Girasis, C; Papadopoulou, K; Ditsios, K; Karvounis, H; Styliadis, I; Parcharidis, G (2010)
To examine left ventricular (LV) function in elite young athletes in relation to structural adaptation to prolonged intense training. Conventional echocardiography and tissue Doppler imaging (TDI) were performed in 15 elite rowers and 12 sedentary matched controls. Rowers had increased LV mass index, septal (12 vs 10 mm, P<0.005) and posterior wall thicknesses (12 vs 9 mm, P<0.001) and increased relative wall thickness. Septal and lateral systolic velocities were enhanced in rowers (septal S(m)=8.5 vs 6.3 cm/s, P<0.001; lateral S(m)=11.4 vs 8.0 cm/s, P<0.005), representing a 35% and 42% increase, respectively. Similarly, septal and lateral early diastolic velocities were enhanced (septal E(m)=12.1 vs 9.5 cm/s, P<0.01; lateral E(m)=16.6 vs 11.6 cm/s, P<0.001), representing a 27% and 43% increase, respectively. Systolic and early diastolic TDI velocities of the lateral wall showed a positive correlation (r=0.65, P<0.01) in athletes indicating a parallel improvement of systolic and diastolic function, while LV stiffness was decreased [(E/E(m))/(LV end-diastolic diameter)=1.13 vs 1.57, P<0.005). Both systolic and diastolic LV function were improved in elite rowers, despite a pattern of concentric hypertrophy.